2006
DOI: 10.1111/j.1464-410x.2006.06006.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin (CD105) expression in human renal cell carcinoma

Abstract: RESULTSOf the tumours, 75% expressed endoglin, and in conventional RCC the expression was inversely correlated to the Tumour-NodeMetastasis (TNM) stage ( P = 0.008) and nuclear grade ( P = 0.01). There was no correlation between endoglin expression and gender, age, tumour size or cell type. Patients with conventional RCC and high endoglin expression had a more favourable prognosis than those with tumours with lower expression ( P = 0.04). A multivariate analysis of prognostic factors showed that TNM stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
6
25
0
2
Order By: Relevance
“…As expected, we found overexpression of Endoglin protein in the endothelium of colon carcinoma tissue, positively correlated with disease progression. These results are in agreement with studies showing that the CD105 + -MVD value is a prognostic marker in colon carcinoma (41,(48)(49)(50), as well as in prostate (51), breast (52,53), kidney (54), esophageal (55,56), head and neck (57,58), uterus (59) and non-small cell lung cancers (60).…”
Section: Discussionsupporting
confidence: 82%
“…As expected, we found overexpression of Endoglin protein in the endothelium of colon carcinoma tissue, positively correlated with disease progression. These results are in agreement with studies showing that the CD105 + -MVD value is a prognostic marker in colon carcinoma (41,(48)(49)(50), as well as in prostate (51), breast (52,53), kidney (54), esophageal (55,56), head and neck (57,58), uterus (59) and non-small cell lung cancers (60).…”
Section: Discussionsupporting
confidence: 82%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 56%
“…21,24,26,28,[62][63][64][65][66] Practically, all studies were based on manual counting of vessels within small areas of tumor utilizing either 'hot-spots' 26,30,67 or small tissue microarray cores. 68 Both factors, small tissue sample and manual input have a large potential for errors; it is logical to replace those methods with standardized computer analyses of large areas. Moreover, the inclusion of an internal reference point is easily achieved by the new methodology and can further increase the accuracy of measurements.…”
Section: Discussionmentioning
confidence: 99%